The predictive role of intolerance of uncertainty and trait of worry in breast cancer patients: A prospective, observational, single-center clinical study - Shams, Malihe; Pardini, Susanna; Del Bianco, Paola; Calabrese, Caterina; De Salvo, Gian Luca; Novara, Caterina (Frontiers in Psychology, 2023)
Background Breast cancer diagnosis and treatment compromise well-being in a pervasive way, and negative consequences may remain after recovery. The psychological side of breast cancer has been extensively investigated; however, the role of intrusive thoughts and intolerance of uncertainty have been studied less systematically. Objectives The present study aimed to prospectively evaluate worry content, depression, anxiety, and post-traumatic stress symptoms and to define the role of the trait of worry and intolerance of uncertainty (IU) related to breast cancer. Methods Patients with their first breast cancer diagnosis were enrolled in a single-center, prospective observational trial. The trait of worry and IU were assessed using the Penn State Worry Questionnaire (PSWQ) and the Intolerance of Uncertainty Scale-Revised (IUS-R). The psychological aspects were evaluated using the Worry Domains Questionnaire (WDQ), the Beck Anxiety (BAI), Beck Depression Inventory-II (BDI-II), and the Impact of Event Scale-Revised (IES-R). Questionnaires were administered in a randomized sequence at diagnosis (T0), 3 months post-diagnosis (T1), and 12 months post-diagnosis (T2). Results One hundred and fifty eligible patients were enrolled in the study and provided the T0 assessment. Further compliance rates were 57% at T1 and 64% at T2. All patients showed a significant and continuous increase in the IES-R scale (p < 0.0001) from diagnosis to the end of the study, while no significant changes were observed for the WDQ, BAI, and BDI-II scales. The clinical PSWQ levels and/or high levels of the IUS-R score were the only variables that aided the distinction between patients who maintain high levels of depression, anxiety, and post-traumatic disorders and those who did not. Conclusion An early assessment of the components of the trait of worry and intolerance of uncertainty could be critical in identifying patients with a higher psychopathological risk. Furthermore, if future studies confirm the present findings, support and monitoring throughout the prognosis may present crucial benefits, and possibly affect the course of treatment.